EMS call center models with and without function differentiation: A comparison. (March 2017) - van Buuren, Martin; Kommer, Geert Jan; van der Mei, Rob; Bhulai, Sandjai
Abstract: In pre-hospital health care the call center plays an important role in the coordination of emergency medical services (EMS). An EMS call center handles inbound requests for EMS and dispatches an ambulance if necessary. The time needed for triage and dispatch is part of the total response time to the request, which, in turn, is a key performance indicator for the quality of EMS. Call center agents should perform the triage efficiently, so that entering calls have short waiting times, and the dispatch of ambulances must be adequate and swift to get a fast EMS response. This paper presents and compares three discrete event simulation models for EMS call centers: the first has two different call center agent classes between whom communication tasks are split, while the second has one class of call center agents that share all tasks. The third model is a combination of both. The models provide new insight into the EMS call center processes and can be used to address strategic issues, such as capacity and workforce planning. The analysis and simulations of urgent communication and decision processes in this paper are valuable to other emergency call centers. 1